The importance of overcoming adversities in increasing group performance in handball, basketball and football - Miguel Ángel López Gajardo; Jose Carlos Poce-Bordón; Jesús Díaz García; Juan José González Pulido (Federación Extremeña de Balonmano; University of Extremadura, 2020)
The main aim of this study was to analyze the relationship between team resilience and group performance in team sports. Participants were 136 handball, basketball and soccer players (17-40 years old; M = 21.12; SD = 5.54), who competed as senior teams from Spanish national leagues. Preliminar analysis and a structural equation modeling was completed to analyze the relationships between the variables. First, the correlation analysis showed a positive association between characteristics of resilience and the group performance, whereas a negative relationship between the vulnerability under pressure with the perceived group performance. Second, the regression analysis showed a positive and significant prediction between resilience characteristics and team performance. However, the prediction between vulnerability under pressure and group performance was not significant. The results specified an initial evidence that establishes a link between team resilience and team performance. Therefore, to create a team that be able to overcoming the adversity during training sessions and competition will have greater perceptions of group performance, thereby improving the collective functioning of the team.